Ranking of Iranian metropolises based on urban smartness index - Somayeh Ghiasy; Sohrab Delangizan; Mohammad sharif Karimi (اقتصاد شهری)
Due to widespread urbanization worldwide, the significant increase in population and its continuous growth have led to numerous challenges, particularly in metropolises, where the concentration of resources exacerbates these issues. Addressing these challenges requires scientific research for effective city management and planning to enhance residents' quality of life. Consequently, city managers and urban planners have emphasized the importance of smart city initiatives to overcome enhance urban living conditions. A smart city is a multidimensional concept encompassing various metrics. This study aims to assess the level of smartness in Iranian metropolises and introduce a composite index for measuring smartness and then ranking and clustering them. To achieve this, 41 variables related to six smart city indicators, including environment, economy, goverment, life, mobility and people were analyzed in 9 Iranian metropolises over years 1385 -1400. The smart city index was derived using analysis the two-stage principal component analysis (PCA) method in the Eviews software, followed by ranking metropolises based on urban intelligence level using the Friedman and Kendall's W test in SPSS software, and finally clustering them using  XLSTAT. The resul indicate that the"environment"index had the most significant impact on smartness indicators. Moreover, among the metropolises in the country, city Tehran ranked highest while city Kermanshah ranked lowest in terms of smart.JEL Classification: C43, C38, O18.